2022
DOI: 10.5194/nhess-22-2185-2022
|View full text |Cite
|
Sign up to set email alerts
|

The determinants affecting the intention of urban residents to prepare for flood risk in China

Abstract: Abstract. In the context of global warming and China's disaster response patterns, it is critical to understand how to promote the effectiveness of household flood protection measures among the public. In this study, we developed a comprehensive theoretical framework based on protection motivation theory (PMT) to identify the main determinants that influence urban residents' intention to prepare for flood risk. In addition to the fundamental factors in PMT, this framework also considered the influence of indiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…The result entails how a person's attitude, such as their attitude when it comes to their knowledge of disaster preparedness and ensuring that their families have a basic knowledge of disaster preparedness, has a significant role when it comes to influencing an individual's intention to prepare. Several other studies have also proven the indicated results; the study conducted by Wang et al [121] confirmed that attitude has a direct effect on an individual's behavioral intention. In this case, it was the intention of an individual to prepare for flood risks in China.…”
Section: Discussionmentioning
confidence: 74%
“…The result entails how a person's attitude, such as their attitude when it comes to their knowledge of disaster preparedness and ensuring that their families have a basic knowledge of disaster preparedness, has a significant role when it comes to influencing an individual's intention to prepare. Several other studies have also proven the indicated results; the study conducted by Wang et al [121] confirmed that attitude has a direct effect on an individual's behavioral intention. In this case, it was the intention of an individual to prepare for flood risks in China.…”
Section: Discussionmentioning
confidence: 74%
“…Generally, when individuals have a more positive attitude toward a specific behavior, they are more likely to engage in that behavior, and vice versa. Therefore, when individuals are faced with the risk of floods, their likelihood of implementing flood prevention measures increases if they have a more positive attitude toward such measures (Wang et al 2022). However, the relationship between attitude towards flood preparedness and intention to prepare can be weakened when individuals have higher levels of trust in public protection.…”
Section: Theoretical Research Frameworkmentioning
confidence: 99%